2021
DOI: 10.3389/fped.2021.660393
|View full text |Cite
|
Sign up to set email alerts
|

Creative Music Therapy and Neurodevelopmental Outcomes in Pre-term Infants at 2 Years: A Randomized Controlled Pilot Trial

Abstract: Impaired neurodevelopment is increasingly recognized as a major health issue in children born prematurely. Creative music therapy (CMT) intends to prevent and or reduce neurobehavioral deficits in pre-term infants using musical stimulation and socio-emotional co-regulation. We conducted a randomized, clinical pilot CMT trial to test feasibility and to examine long-term neurodevelopmental outcomes in pre-term infants (NCT02434224: https://clinicaltrials.gov/ct2/show/NCT02434224). Eighty-two pre-term infants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 62 publications
3
19
0
3
Order By: Relevance
“…In terms of long‐term development, we found no substantial CMT treatment effect on language, cognitive and motor outcomes measured with Bayley‐III in EPTs at 2 years, consistent with three other small studies investigating the long‐term effect of music interventions in preterm infants 10,11,21 . Interestingly, these results contrast their primary trials' outcomes showing significantly enhanced brain network development 8,9 and neural processing of speech sound changes 22 at term equivalent age associated with better long‐term language and cognitive outcomes in these trials.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of long‐term development, we found no substantial CMT treatment effect on language, cognitive and motor outcomes measured with Bayley‐III in EPTs at 2 years, consistent with three other small studies investigating the long‐term effect of music interventions in preterm infants 10,11,21 . Interestingly, these results contrast their primary trials' outcomes showing significantly enhanced brain network development 8,9 and neural processing of speech sound changes 22 at term equivalent age associated with better long‐term language and cognitive outcomes in these trials.…”
Section: Discussionsupporting
confidence: 87%
“…18 However, 2 years later, participation rates in the follow-up assessments were high (87.1%) and moderate (58.1%) 5 years later. This high-attrition rate is consistent with our consecutive RCT 10 and the general attendance rates for follow-up examinations in other countries. 19 One explanation and thereby bias may be that parents of children who develop well often skip the follow-up examinations, 20 whereby in our sample, some other reasons for non-compliance were that families moved abroad and were no longer reachable.…”
Section: Neurodevelopmental Outcomes At the Corrected Age Of Five Yearssupporting
confidence: 90%
“…Our findings were in line with other recent studies that showed similarly beneficial short-term effects of neonatal music interventions at term age [15][16][17] without long-term benefits. 18,19 These results imply that early music interventions may not improve long-term outcomes in preterm-born children, proposing more sustained interventions to be implemented and investigated. However, it should be considered that the sensitivity of Bayley-III has been criticised.…”
Section: Discussionmentioning
confidence: 99%
“…Recorded music 15,16 and infant‐directed lullaby singing offered by a trained music therapist, 17 in turn, have been shown to support brain development by promoting functional network connectivity at term age. However, no effects of these music interventions on neurodevelopmental outcomes were found at 12 and 24 months of age 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…Interventions to attenuate stress and stabilize the infant during this crucial phase hold promise to either prevent or attenuate damage to the developing brain. Research investigating long-term effects of music therapy is only evolving [ 7 , 8 ] but vital sign responses to music therapy as a surrogate parameter of short term-stabilisation has been well-studied [ 9 , 10 , 11 ]. Currently, the optimal setting in which music therapy should be applied is under investigation [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%